2015
DOI: 10.1620/tjem.236.71
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemic, Hypolipidemic and Antioxidant Effects of Peptides from Red Deer Antlers in Streptozotocin-Induced Diabetic Mice

Abstract: Diabetes mellitus is a serious chronic metabolic disorder. To develop novel anti-diabetic drugs from nature sources has always been the focus of research. Red deer (Cervus elaphu Linnaeus) antler is one of the most famous Chinese traditional medicines. We found that the peptides of 5-10 kDa from red deer antlers (PRDA) promoted the growth of cultured rat islet cells. The purpose of this study was to investigate the anti-diabetic actions of PRDA in vivo and purify a pure active peptide. We therefore investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 29 publications
2
15
0
1
Order By: Relevance
“…In the present study, the mean plasma TAC level in the DC group was significantly decreased in comparison with the NC group ( Figure 5 ). This finding coincides with the other studies which reported that diabetes was associated with reduced levels of antioxidant activity in the blood and tissues of diabetic animals [ 40 , 41 ]. The reduced mean plasma TAC level in the DC group might indicate that there was an imbalance between free radical formation and antioxidant protection as a consequence of increased utilization of endogenous antioxidants in response to the elevated levels of free radicals [ 16 ].…”
Section: Resultssupporting
confidence: 93%
“…In the present study, the mean plasma TAC level in the DC group was significantly decreased in comparison with the NC group ( Figure 5 ). This finding coincides with the other studies which reported that diabetes was associated with reduced levels of antioxidant activity in the blood and tissues of diabetic animals [ 40 , 41 ]. The reduced mean plasma TAC level in the DC group might indicate that there was an imbalance between free radical formation and antioxidant protection as a consequence of increased utilization of endogenous antioxidants in response to the elevated levels of free radicals [ 16 ].…”
Section: Resultssupporting
confidence: 93%
“…Dietary antioxidants offer protection against ROS-/RNS-induced stress and damage through their direct actions based on mechanisms complementary to the functions of enzymatic antioxidants in the human body as well as their close association and support to primary and secondary enzymes (Durackova, 2010). Among these antioxidant species, antioxidative polysaccharides extracted from various raw materials in nature and their derived products have attracted increasing attention (Li et al, 2014;Jiang et al, 2015;Rangika et al, 2015). Among these antioxidant species, antioxidative polysaccharides extracted from various raw materials in nature and their derived products have attracted increasing attention (Li et al, 2014;Jiang et al, 2015;Rangika et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…There are many dietary antioxidants that can be sourced from nature including protein-, polysaccharide-or lipid-based substances and small molecule phytochemicals such as vitamins and polyphenols (Lobo et al, 2010;Nimse & Pal, 2015). Among these antioxidant species, antioxidative polysaccharides extracted from various raw materials in nature and their derived products have attracted increasing attention (Li et al, 2014;Jiang et al, 2015;Rangika et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Помимо антиоксидантного эффекта пептидов, выделенных из пантов марала, были изучены также гипогликемические и гиполипидемические эффекты продуктов пантового оленеводства [5]. Показано, что компоненты продуктов пантового олене-водства оказывают иммуномодулирующее действие [6], также был отмечен гемопоэти-ческий эффект [7].…”
Section: казанский медицинский журнал 2018 г том 99 №1unclassified